Social Clauses in Public Procurement as a Form of Support for the Social Economy Entities - Moroń, Dorota (Studia Oeconomica Posnaniensia, 2019)
Due to the social utility of social economy entities, their role in the social and vocational activation of people at risk of social exclusion and providing social services, an important aspect of public activities is, in accordance with the principle of subsidiarity, the support for the social economy sector by creating conditions for the social economy entities’ activity development. One of the possibilities is facilitating the obtainment of public procurement through the use of social clauses. These are solutions used in public procurement, which allow procurers to take into account important social aspects in procurement, promote the idea ofequalizing opportunities and the socio-vocational integration of people at risk of social exclusion. The aim of the article is to analyze the usefulness of social clauses as a form of support for social economy entities. The article presents an analysis of the usefulness of social clauses in supporting social economy entities considered from a formal and legal perspective and presents the use of this mechanism by local governments and social economy entities from the Dolnośląskie, Lubuskie, Opolskie and Wielkopolskie regions. The analysis was based on the results of research conducted as part of the "Skuteczni w zamówieniach publicznych" project, implemented by the "Merkury" Foundation and financed from the European Social Fund under the operational program "Knowledge Education Development 2014-2020".